Abuso del derecho en los contratos artesanales de operarios y aprendices para obtener beneficios patronales. - Pinta Songor, Michelle Elizabeth (2022)
The present thesis is entitled: "ABUSE OF THE LAW IN THE CRAFTSMAN CONTRACTS OF OPERATORS AND APPRENTICES TO OBTAIN EMPLOYER BENEFITS", and its interest to develop is due to the abusive use of the artisan qualification that many workshop masters make ,thanks to the contribution of several specialists it could be found that in many cases the employer abuses the benefits granted by the artisan qualification conferred by Junta Nacional de Defense del Artisan to evade labor rights by issuing artisan contracts to workers who have not been trained in the craftsmanship, Currently, the Artisan's Defense Law has not undergone transcendental modifications to ensure the labor rights of artisans, much less to generate new rights and benefits according to the current needs of artisans, such as the promotion of scholarships, exchanges and economic recognition for outstanding artisans. In the present thesis, materials and methods were applied that allowed the development of the investigation, as well as ten interviews and thirty surveys to professionals of labor law, artisan, corporate and popular and solidarity economy, results that served to propose the project of legal reform to the Labor Code so that the labor rights of workers are not undermined, such as a fair remuneration, The results were useful to propose the legal reform project to the Labor Code so that the workers' labor rights are not undermined, such as a fair remuneration, a decent salary, thirteenth and fourth remuneration, and new benefits such as scholarships, exchanges and promotion of artisan work are included, benefits that contribute so that the artisans generate enterprises that go from small to medium scale and then to large scale so that they contribute with greater contribution to the country's economy, with the payment of taxes and generate sources of employment. Key words: Artisan Contract, Workshop Master, Operator, Apprentice, Labor Code and Artisan's Defense Law.